Genome-wide identification and expression profiling analysis of ZmPIN, ZmPILS, ZmLAX and ZmABCB auxin transporter gene families in maize (Zea mays L.) under various abiotic stresses. - Runqing Yue; Shuanggui Tie; Tao Sun; Lei Zhang; Yanjun Yang; Jianshuang Qi; Shufeng Yan; Xiaohua Han; Huizhong Wang; Chenjia Shen (PLoS ONE, 2015)
The auxin influx carriers auxin resistant 1/like aux 1 (AUX/LAX), efflux carriers pin-formed (PIN) (together with PIN-like proteins) and efflux/conditional P-glycoprotein (ABCB) are major protein families involved in auxin polar transport. However, how they function in responses to exogenous auxin and abiotic stresses in maize is largely unknown. In this work, the latest updated maize (Zea mays L.) reference genome sequence was used to characterize and analyze the ZmLAX, ZmPIN, ZmPILS and ZmABCB family genes from maize. The results showed that five ZmLAXs, fifteen ZmPINs, nine ZmPILSs and thirty-five ZmABCBs were mapped on all ten maize chromosomes. Highly diversified gene structures, nonconservative transmembrane helices and tissue-specific expression patterns suggested the possibility of function diversification for these genes. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to analyze the expression patterns of ZmLAX, ZmPIN, ZmPILS and ZmABCB genes under exogenous auxin and different environmental stresses. The expression levels of most ZmPIN, ZmPILS, ZmLAX and ZmABCB genes were induced in shoots and were reduced in roots by various abiotic stresses (drought, salt and cold stresses). The opposite expression response patterns indicated the dynamic auxin transport between shoots and roots under abiotic stresses. Analysis of the expression patterns of ZmPIN, ZmPILS, ZmLAX and ZmABCB genes under drought, salt and cold treatment may help us to understand the possible roles of maize auxin transporter genes in responses and tolerance to environmental stresses.